Critical Discourse Analysis of the Narrative of Women's Emancipation in Arab Patrialkal Culture - Qotrunnada, Maulida Hasbiya; Hakim, Arief Rahman (LINGUA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The difference in rights and freedoms between women and men is a form of injustice or discrimination, as happened in Arab society. This was formed due to cultural factors and ancient thinking of the community, which was able to hinder the progress or emancipation of women until now. The injustice is in the form of women's limitations in family and political law. From these problems, the majority of women and activists who support women, try to increase emancipation and fight for women's rights again. From this statement, the researcher aims to reveal the intention of a news article entitled سؤال تحرر المرأة المُتَجَدِّد by Kamal Abdullatif on the online magazine website Al-Arabi. The analysis was carried out using a descriptive qualitative method with a read-note data collection technique. Meanwhile, the approach used in this study is Sara Mills' critical discourse analysis, which provides an understanding of the position of the subjects and the involvement of the reader in the discourse. The results of the analysis show that there is an interest from the author of the article, Kamal Abdullatif, to invite readers to participate in supporting women's emancipation. This research is expected to be the basis for further research to examine similar objects and issues more deeply, so that it can enrich the discourse and strengthen efforts in upholding gender equality.